Efforts to Minimize Work Accidents at PT. Behavior Based Safety (BBS) Method - Naufal Nibraas Nabiiah Harijadi; Ardhan Firman Mardyansyah; Vanesa Vanes; Zahra Syifa; Nanda Dwi Cahyani; Epy Handayani; Gilang Ramadan (Riviera Publishing, 2024)
PT. X is a company engaged in the automotive sector, focusing on truck repair. The purpose of this report is to minimize work accidents through a behavior-based safety (BBS) approach at PT. X. The Behavior Based Safety (BBS) program is an approach to safety based on human behavior. It aims to increase employee awareness, involvement, and responsibility to create a safe working environment. The BBS program at the company aims to improve employee compliance and change work behaviors. The method used in the behavior-based safety approach is called DO IT. The DO IT method consists of 4 steps: Define, Observe, Intervene, and Test. The research was conducted using a qualitative method involving in-depth interviews with workshop management, direct observation, and analysis of documents related to BBS implementation. The results of the research indicate that the implementation of BBS will significantly contribute to improving the performance of the automotive workshop.